Advanced techniques for gene heterogeneity research: Single‐cell sequencing and on‐chip gene analysis systems. Issue 1 (31st January 2022) - Dong, Zaizai; Wang, Yu; Yin, Dedong; Hang, Xinxin; Pu, Lei; Zhang, Jianfu; Geng, Jia; Chang, Lingqian
Abstract: Gene heterogeneity leads to the differences in cellular behaviors in a wide range, such as tumor drug‐resistant mutation, epithelial‐mesenchymal transition, and migration, posing significant challenges to the development of biomedicine. Traditional gene analysis methods, such as polymerase chain reaction, employ a mass of cells as the gene source, resulting in that the gene properties from a specific single cell are hidden in massive gene information. Recent decades have seen the emerging single‐cell gene analysis techniques with their unprecedented opportunities to study gene heterogeneity with high precision and high throughput. In this review, we summarized the state‐of‐the‐art techniques for single‐cell sequencing and on‐chip gene analysis systems. The principles of each technique are introduced in detail, with the focus on the application scenarios in gene heterogeneity research. Looking forward, we also introduced the challenges in current technologies and point out the future direction for facilitating the technical improvement and clinical applications of single‐cell gene analysis techniques. Abstract : Fully understanding the subtle gene differences among single cells is crucial for decoding gene heterogeneity. In this review, the authors have systematically introduced the recent advances in both single‐cell sequencing techniques and on‐chip single‐cell gene analysis systems, expecting to promote the study of gene heterogeneity and provide references for precision medicine.